Retinal detachment in albinism - Mansour AM (Dove Medical Press, 2018)
Ahmad M Mansour,1,2 Jay Chhablani,3 J Fernando Arevalo,4,5 Lihteh Wu,6 Ravi Sharma,3 Suthasinee Sinawat,7 Tharikarn Sujirakul,8 Alexandre Assi,9 Wandsy M Vélez-Vázquez,10 Mohamad A Mansour,1 Ozcan Kayikcioglu,11 Cem Kucukerdonmez,12 Ali Kal13 1Department of Ophthalmology, American University of Beirut, Beirut, Lebanon; 2Department of Ophthalmology, Rafic Hariri University Hospital, Beirut, Lebanon; 3L.V. Prasad Eye Institute, Banjara Hills, Hyderabad, India; 4Department of Ophthalmology, Johns Hopkins Bayview Medical Center, Baltimore, MD, USA; 5Wilmer Eye Institute, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 6Asociados de Macula Vitreo y Retina de Costa Rica, San José, Costa Rica; 7Department of Ophthalmology, Srinagarind Hospital, Khon Kaen University, Khon Kaen, Thailand; 8Department of Ophthalmology, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 9Beirut Eye and Ear Specialty Hospital, Beirut, Lebanon; 10Retina Associates, Guaynabo, Puerto Rico; 11Celal Bayar University, Manisa, Turkey; 12Ekol Eye Hospital, Izmir, Turkey; 13Department of Ophthalmology, Baskent University, Konya, Turkey Purpose: To report the visual and anatomic outcomes of albino retinal detachment (ARD) repair. Methods: Collaborative retrospective analysis of ARD. Outcome measures were number of surgical interventions, final retinal reattachment, and best corrected visual acuity (BCVA) at last follow-up. Results: Seventeen eyes of 16 patients (12 males; mean age =37.8 years) had the following complications at presentation: macula off (14), total (7) or inferior detachment (5), proliferative vitreoretinopathy (5), detectable break (16), lattice (5), horseshoe tears (9), and giant tear or dialysis (4). Mean number of interventions was 1.8 (range =1–5) and included cryopexy (15) with scleral buckle (11), and/or vitrectomy (8). Mean initial BCVA was counting finger (CF) 1 m and at last follow-up (mean 77 months) CF4m with mean improvement of 4.5 lines (early treatment diabetic retinopathy study) (P=0.05). Intraoperative choroidal hemorrhage occurred in three eyes. The retina was finally attached in 14 eyes, with residual inferior detachment in three eyes with silicone oil in situ. Silicone oil was kept in six of seven eyes because of residual inferior detachment (3) and removal of silicone oil, which led to redetachment (1) or fear of redetachment (2). Conclusion: Repair of ARD may require several interventions, with the need to keep silicone oil in several cases due to nystagmus and reduced melanin pigment. Keywords: cryopexy, foveal hypoplasia, nystagmus, retinal detachment, scleral buckle, silicone oil, vitrectomy